Association between clustering of cardiovascular risk factors and left ventricular geometric remodeling in Chinese children - Liu, Qin; Wang, Huan; Zhao, Min; Zhang, Cheng; Bovet, Pascal; Xi, Bo (Frontiers in Cardiovascular Medicine, 2023)
Background: Several cardiovascular (CV) risk factors are reported to be associated with abnormal cardiac structure in children and adults. However, no study has assessed the association between clustering of multiple CV risk factors and left ventricular geometric (LVG) remodeling. We examined the association between clustering of CV risk factors and LVG remodeling among Chinese children. Methods: This cross-sectional study included 1406 children aged 6-11 years. Clustering of CV risk factors was quantified as the sum of the number of five CV risk factors (abdominal obesity, elevated blood pressure, high fasting blood glucose, high triglycerides and low high-density lipoprotein cholesterol). Based on left ventricular mass index and relative wall thickness (RWT), left ventricular hypertrophy (LVH), high RWT and LVG remodeling [concentric remodeling (CR), eccentric hypertrophy (EH) and concentric hypertrophy (CH)] were defined. Results: Compared to participants without CV risk factor, those with 1, 2 and ≥3 risk factors were at increased risk of LVH [ORs (95% CIs): 3.49 (2.19-5.56), 5.53 (3.20-9.55), and 19.19 (9.67-38.08), respectively]; corresponding values for high RWT were 2.47 (1.63-3.74), 3.76 (2.25-6.27), and 5.47 (2.65-11.28). Similar associations between clustering of CV risk factors and LVG remodeling were found [CR: 1.71 (1.06-2.76), 2.83 (1.54-5.18), and 3.82 (1.37-10.62); EH: 2.42 (1.42-4.11), 4.23 (2.24-7.96), and 16.86 (7.70-36.92); CH: 14.92 (4.41-50.47), 23.15 (6.32-84.83), and 71.19 (17.09-296.56)]. Conclusion: CV risk factors in isolation and combination were associated with an increased risk of LVH, high RWT and LVG remodeling among children, emphasizing the need to consider multiple risk factors when assessing the risk of cardiac outcomes.